Knowledge, Attitude and Practices towards Utilization of Implants among women aged 15-45 years attending Bunapongo Health Centre III, Mbale District. A Cross-section Study. - Mulekhwa , Joel; Nakasolo , Sania (Student’s Journal of Health Research Africa, 2022)
Background: The purpose of the study is to determine the knowledge, attitude, and practices towards utilization of implants among women aged 15-45years attending Bunapongo HCIII, Mbale district. Methodology: The study employed a cross-section study for quantitative data targeting 50 women aged 15-45years using simple random sampling and semi-structured questionnaires as data collection tools. Questionnaires were first pre-tested before giving them to respondents to fill. Data were analyzed manually and presented in tables and figures. Results: 70% of the respondents had ever heard about implant contraceptives, most respondents (43%) got the information from friends and less than half of the respondents (40%) knew the right site for administration of implants and duration for effective protection against pregnancy was known by 50% of the respondents however more than half of the respondents (70%) claimed that implants had side effects, over bleeding was the highly-rated side effect (43%). 78% of the respondents agreed that implants prevent the occurrence of pregnancy, 70% of the respondents said partners should not be involved in choosing the contraceptive method to use and 70% of the respondents said they would not use implants. Only 20% of the respondents were using implants as their contraceptive method at the time of the study. Conclusion: The study concluded that women had poor knowledge, a negative attitude, and poor practices towards the utilization of implants. Recommendation: The researcher recommended that the MoH should continuously educate women and their partners about the advantages and benefits of using LARC methods like implants, health workers should clearly explain to the women the side effects and reassure them that they can be managed and they should also do outreaches to capture a large number of women.